Cultivation of Prevotella copri in a medium supplemented with tomato juice suppresses the bacteria-induced intestinal permeability in Caenorhabditis elegans - Nobuo Fuke; Natsumi Desaka; Yuichiro Nakazawa; Shigenori Suzuki; Kenji Matsumoto; Yasuki Higashimura (PLoS ONE, 2025)
Epidemiological studies in humans have suggested that tomato consumption and the compositional ratios of Prevotella, Megamonas, and Streptococcus in the intestinal microbiota are related to intestinal permeability. In this study, we investigated the causal relationship using Caenorhabditis (C.) elegans. We cultured Escherichia coli OP50 (the standard C. elegans food), Prevotella (P.) copri JCM 13464T, Megamonas funiformis JCM 14723T, and Streptococcus salivarius JCM 5707T in either normal medium or medium containing 1% (v/v) tomato juice (TJ medium), fed these bacteria to C. elegans for three days, and evaluated intestinal permeability using the Smurf assay. The proportion of Smurf individuals was significantly lower in C. elegans fed P. copri cultured in TJ medium than in those fed the same bacteria cultured in normal medium, while other strains showed no such medium-dependent differences. Interestingly, heat-killed P. copri grown in normal medium also reduced the proportion of Smurf individuals. Furthermore, P. copri grown in TJ medium exhibited a lower survival rate after seeding on nematode growth medium, an effect not observed in other strains. Liquid chromatography-tandem mass spectrometry analysis revealed that P. copri cultured in TJ medium accumulated L-(-)-3-phenyllactic acid (L-(-)-3-PLA), a compound known for its antibacterial properties through oxidative stress and its protective effects on the intestinal barrier. In contrast, the levels of known antioxidants such as 2,3,4,9-tetrahydro-1H-β-carboline-3-carboxylic acid and Cyclo(phenylalanyl-prolyl) were decreased. Culturing P. copri in normal medium supplemented with L-(-)-3-PLA alone did not reduce survival, suggesting that both L-(-)-3-PLA accumulation and the depletion of antioxidants contribute to reduced viability. Additionally, L-(-)-3-PLA directly suppressed intestinal permeability in C. elegans. In conclusion, the results of this study suggest that TJ may inhibit increased intestinal permeability through both rendering P. copri vulnerable and the direct effects of L-(-)-3-PLA. Further studies are needed to determine the relevance of these findings to humans.